Favouring inhibitory synaptic drive mediated by GABAA receptors in the basolateral nucleus of the amygdala efficiently reduces pain symptoms in neuropathic mice. (17th March 2016) - Zeitler, Alexandre; Kamoun, Nisrine; Goyon, Stéphanie; Wahis, Jérôme; Charlet, Alexandre; Poisbeau, Pierrick; Darbon, Pascal
Abstract: Pain is an emotion and neuropathic pain symptoms are modulated by supraspinal structures such as the amygdala. The central nucleus of the amygdala is often called the 'nociceptive amygdala', but little is known about the role of the basolateral amygdala. Here, we monitored the mechanical nociceptive thresholds in a mouse model of neuropathic pain and infused modulators of the glutamate/GABAergic transmission in the basolateral nucleus of the amygdala (BLA) via chronically‐implanted cannulas. We found that an N ‐methyl‐D‐aspartate‐type glutamate receptor antagonist (MK‐801) exerted a potent antiallodynic effect, whereas a transient allodynia was induced after perfusion of bicuculline, a GABAA receptor antagonist. Potentiating GABAA receptor function using diazepam or etifoxine (a non‐benzodiazepine anxiolytic) fully but transiently alleviated mechanical allodynia. Interestingly, the antiallodynic effect of etifoxine disappeared in animals that were incapable of producing 3α‐steroids. Diazepam had a similar effect but of shorter duration. As indicated by patch‐clamp recordings of BLA neurons, these effects were mediated by a potentiation of GABAA receptor‐mediated synaptic transmission. Together with a presynaptic elevation of miniature inhibitory postsynaptic current frequency, the duration and amplitude of GABAA miniature inhibitory postsynaptic currents were also increased (postsynaptic effect). The analgesic contribution of endogenous neurosteroid seemed to be exclusively postsynaptic. This study highlights the importance of the BLA and the local inhibitory/excitatory neuronal network activity while setting the mechanical nociceptive threshold. Furthermore, it appears that promoting inhibition in this specific nucleus could fully alleviate pain symptoms. Therefore, the BLA could be a novel interesting target for the development of pharmacological or non‐pharmacological therapies. Abstract : Basolateral amygdala (BLA) infusions of EFX and MK801 reduce pain symptoms in neuropathic rat. EFX by increasing inhibition and MK801 by decreasing excitation lead to an imbalance of excitation‐inhibition balance in favor of inhibition in BLA. EFX action on GABAergic synaptic transmission is dependent on neurosteroid production.